Prove that if N=abc+1, then (N,a)=(N,b)=(N,c)=1.
The Attempt at a Solution
Assume N=abc+1. We must prove (N,a)=(N,b)=(N,c)=1. Proceeding by contradiction, suppose (N,a)=(N,b)=(N,c)=d such that [tex] d\not=1 [/tex]. Then we know, d | N and d | abc. Thus, from our assumption, we see that d | 1, a contradiction.
Is this a valid argument? Also, what is another way to prove this without using contradiction? Thanks, this is my first class with proofs. Also, I know "if (a,b)=d, then ax+by=d." Is the converse true?